Is allelopathy from winter cover crops affecting row crops?. Issue 1 (15th May 2020) - Koehler‐Cole, Katja; Everhart, Sydney E.; Gu, Yan; Proctor, Christopher A.; Marroquin‐Guzman, Margarita; Redfearn, Daren D.; Elmore, Roger W.
Abstract: Cover crops (CC) have been explored in corn ( Zea mays L.), cotton ( Gossypium hirsutum L.), soybean [ Glycine max (L.) Merr.], and wheat ( Triticum aestivum L.) systems for their allelopathic potential to control weeds. However, allelopathic compounds may negatively affect these row crops by reducing germination, emergence, and grain yields. We reviewed studies that document allelopathic effects of CC on subsequent row crops in field and laboratory settings. We summarize the influence of CC management, including biomass production, planting and termination timing on allelochemical quantity. Our review found few studies documenting allelopathic effects of CC on row crops in field settings. Studies that focus on understanding yield impacts of CC on row crops should be designed to include allelopathic CC–row crop interactions. Understanding the link between CC management and allelopathic dynamics can help avoid impacts on the growth and productivity of the subsequent row crop.